Comparing block characteristics of mixtures of short/intermediate- and long-acting local anesthetics for peripheral nerve block: a systematic review and meta-analysis - Cheng Lin; Ana Larissa Guerrero; Joshua Jesin; Rohin Tangri; Nasong Anthony Luginaah; Kamal Kumar; Christopher Hansebout (Brazilian Journal of Anesthesiology)
Introduction: Results from Randomized Controlled Trials (RCTs) on mixed Local Anesthetics (LA) are conflicting. We conducted a systematic review and meta-analysis on whether using mixed LA leads to faster onset of surgical block. Method: We conducted systemic review and meta-analysis of RCTs. Medline and Embase without language restriction from inception to June 15, 2024, were searched. Included RCTs had to compare mixed LA to long-acting LA in adult surgical patients for onset or duration of nerve blocks. Onset time to surgical block was the primary outcome. The Cochrane Risk of Bias Tool with GRADE methodology was utilized to assess evidence quality. Results: Nineteen trials including 1060 participants met the inclusion criteria. Mixed LA modestly reduced time to surgical block (-8.4 minutes; 95% CI -12.0 to -4.8 minutes; p = 0.0001; I2 = 0.99), sensory block duration (-226.2 minutes; 95% CI -352.2 to -100.1 minutes; p = 0.002; I2 = 0.98) and motor block duration (-259.2 minutes; 95% CI -399.5 to -119.0 minutes; p = 0.003; I2 = 0.98) but not time to analgesic request duration (-130.5 minutes; 95% CI -265.9 to 4.9 minutes; p = 0.057; I2 = 0.98). GRADE scoring ranged from low to very low. Conclusion: The existing evidence showed mixed LA led to a modest reduction in surgical block latency but also shortened block duration. Future studies should evaluate the role of mixed LA in lower limb blocks and optimal dosing of long-acting LA to balance onset latency and analgesic duration. PROSPERO registration: CRD42024552801.